(untitled) (The Pakistan Development Review, 2014)
Cash transfer programmes are widely considered a ‘magic bullet’ for reducing poverty. Whether they actually have such an incredible impact on poverty reduction is debatable but they surely are gaining credibility as an effective safety net mechanism and consequently an integral part of inclusive growth strategies in many developing countries. As shown by Ali (2007), inclusive growth rests on three basic premises. First, productive employment opportunities should be created to absorb labour force. Second, capability enhancement and skill development should be focused in order to broaden people’s access to economic opportunities. And lastly, a basic level of well-being has to be guaranteed by providing social protection. Safety nets are at the core of the last pillar, provided mainly through cash transfers, which can be both conditional and unconditional.